Measuring the impact of corrective exercises on ankle function in collegiate female soccer players - Gutierrez, A. C.; Lininger, M. R. (International Journal of Athletic Therapy & Training, 2019)
Injuries to the ankle joint in soccer athletes are extremely common. Twenty-two female collegiate soccer athletes performed ankle corrective exercises for 3 months to attempt to establish and maintain optimal ankle joint function. The corrective exercises were devised to improve ankle range of motion (ROM) and Star-Excursion Balance Test (SEBT) scores. Statistically significant improvements were seen in ankle ROM and in the SEBT for the posteromedial, posterolateral, and composite reach portions of the test; the anterior reach direction failed to show significant changes. These results have clinical implications which suggest that corrective exercises may promote optimal ankle joint function and potentially reduce the risk of injury to the ankle.